Lights In - A Business Plan (Confidential) - Dunn, Matthew J. (2015)
Lights In is a radically efficient lighting services enterprise for businesses. Our primary function will be to convert SMEs to more energy efficient light bulbs and/or fittings prior to the phasing out of halogen bulbs in 2018 or before they need to replace them due to expiry of their lifespan. Cost savings will be immediately apparent, and all customer investment will be recouped within two years. Not only will our service substantially reduce business energy consumption, it will enable our customers to qualify for efficiency-based funding, loans and tax relief. Our consultancy will manage the whole process for them, from a lighting design service to maximising the effects of artificial lighting, to installation, to the development of Energy Management Systems and to the application for and accessing of financial incentives and tax breaks. Our business is scalable. We will outsource installation until sufficient sales are apparent and then employ trainees until they qualify and can manage on their own. Our costs correlate to the amount of custom we develop, and we can pause or grow swiftly according to demand. We are the only consultancy that offers such a holistic package at such a competitive rate. We are open to partnerships, alliances and publicity in order to promote the value of energy efficiency. Our experience of running a start-up limited company for the last 9 years and our contacts within the service sector and the East Midlands will enable us to make a significant impact with this new venture. Our target market is primarily service sector related businesses, of which there are 12,000 in the East Midlands alone that meet our criteria. We have tailored our offer for the target market based on our extensive primary and secondary research. Our findings have also confirmed that there is strong interest in our consultancy and services. We have purposefully created a lean business so that we can maintain low costs and pass these on to our customers. We have identified a business model that will encourage businesses to make the change to energy efficient lighting and to do this we must operate on a low cost and low charge basis. We forecast that we will break-even by the end of the first quarter and stabilise before 18 months. By the end of the third year we anticipate employing a further five staff and having profit before tax of over £120,000. To achieve these goals we will need to source £15,000 in funds by our second month in business for lighting inventory and our minimal running costs. This will be added to the £5,000 we will personally invest.